Auxin and vesicle traffic - Robinson, David G.; Hillmer, Stefan (Plant physiology, 2018)
Dear Editor, - - The plant hormone auxin (indole-3-acetic acid [IAA]) controls almost every aspect of plant development and growth. Auxin is transported within the plant from cell to cell through auxin transporters, including the PIN-FORMED (PIN) efflux transporters ([Geisler et al., 2017][1]; [